TEING HANG KOLANG SEBAGAI PENDIDIKAN EKOESKATOLOGIS: MERAWAT KOSMOS DALAM TERANG TRADISI - Harjon, Losianus; Ware Mere, Henokh Albert; Loge, Maria Claritas; Fallo, Fridolin Mawangsuri; Dampul, Martinus; Brili Egus, Petrus Dewantara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Teing Hang Kolang rite is an important traditional practice of the Manggarai community that sustains the continuity of relationships between humans, nature, and ancestors to the present day. This study aims to explore and reinterpret the rite from an eschatological perspective, offering deeper insight into the relationship between human beings and creation as part of the journey toward the fullness of life. It finds that the rite embodies eschatological meaning and spiritual dimensions that affirm the interconnectedness of the human world, the spiritual realm, and cosmic harmony. Using a descriptive method through in-depth remote interviews and literature review, the research shows that the rite is not merely a routine act of honoring ancestors, but a religious practice that connects humans with God as Creator through concrete actions such as maintaining balance and harmony with nature. Consequently, the Teing Hang Kolang rite represents a form of contextual theology rooted in the lived experience of the Manggarai people, emphasizing that salvation is not only spiritual liberation but also the renewal of all creation, while integrating ancestral memory, ecological harmony, and a holistic vision of the future ##default.groups.name.author## Edit Delete SettingsHenokh Albert Ware Mere merehenokhetty@gmail.com ##default.groups.n